Incidental Krukenberg Tumor During Cesarean Section - Victor Delgado-Lazo; Rizwana Syed; Kelley B. Mowatt; Andrea Popescu-Martinez (Annals of Internal Medicine: Clinical Cases)
We present the case of a 29-year-old woman in her 30th week of pregnancy admitted for preterm contractions. She had an emergent cesarean delivery and was noted to have a large ovarian mass diagnosed on pathology as a Krukenberg tumor. Subsequent upper gastrointestinal endoscopy revealed gastric signet ring cell adenocarcinoma as the primary cancer. The patient received palliative chemotherapy and immunotherapy and is pending clinical trial participation. Pregnancy-associated gastric cancer is a rare condition with a poor prognosis as most symptoms may be attributed to a normal pregnancy. This misinterpretation often leads to a late diagnosis and poor outcomes.